The establishment process of Gunung Halimun National Park resulted in tenurial insecurity for local people, farmers, and hunters. This condition leads to the open conflict between local people and the government. One of the issues that make local people fight for is their rights to have an access and control toward the resources. As a development model of sustainable tourism, ecotourism has been used to respond this type of conflict. The aims of this study were to evaluate whether or not the - Sudhiani Pratiwi; Hadi S. Alikodra; Soehartini Sekartjakrarini; Hariadi Kartodihardjo (Forum Pasca Sarjana, 2008)
The establishment process of Gunung Halimun National Park resulted in tenurial insecurity for local people, farmers, and hunters. This condition leads to the open conflict between local people and the government. One of the issues that make local people fight for is their rights to have an access and control toward the resources. As a development model of sustainable tourism, ecotourism has been used to respond this type of conflict. The aims of this study were to evaluate whether or not the ecotourism development in the case study perform the ideal criteria of ecotourism concept and to determine how the existing institutional arrangement support the fulfillment of the criteria. Two analytical methods were used to achieve these goals. They were analysis of the performance of ecotourism criteria and institutional analysis of ecotourism development (consists of stakeholder analysis, need analysis and policy analysis). The results of ecotourism assessment showed that the ecotourism development in the case study do not fulfill the ideal criteria of ecotourism. While the result of institutional analysis indicated three main findings, namely, insufficient rules and policy to guide ecotourism development, unequal role between stakeholders of ecotourism development, and lack of accountability in implementing the roles in the study area. This study suggests that in order to perform the ideal ecotourism development, stakeholders should develop agreed local ecotourism policy, reinforce existing organization and improve the capacity of human resources. Key words: ecotourism, institution, national park, policy analysis, qualitative analysis